Novel Semiotics Analyst Yang Telah Lama Pergi by Tere Liye - Tasya Nidea Putri; Sri Rahayu (Jurnal Sastra Indonesia, 2025)
The semiotic study in the novel Yang Have Long Gone by Tere Liye expresses signs in the text to form a more profound meaning through symbols, icons, and indices. This novel contains many symbols, icons, and indexes that create a system of interconnected signs through dialogue, descriptions, and events. Thus, semiotic studies understand how this novel's signs interact to create a more complex meaning. The problem formulation in this research is the semiotic elements of the icon, index, and symbol aspects in the novel Yang Lama Lagi by Tere Liye. This research aims to describe, analyze, and conclude the signs, which include the icon, index, and symbol aspects. This research's benefit is understanding and defining semiotic theory through icons, indices, and symbols in literary works. This research uses a qualitative approach with descriptive methods. The data collection technique used in this research is hermeneutics: reading, taking notes, and concluding. The results of this research show that in the novel Yang Has Long Gone by Tere Liye, some signs include aspects of icons, indexes, and symbols. There are 12 data for the icon aspect, 54 for the index aspect, and 34 for the symbol aspect. In this research, it can be concluded that the index aspect that is most often found in the novel Yang Has Long Gone by Tere Liye, this aspect is related to the causal and cause-effect relationships that arise in the cultural context of the characters in the novel Yang Has Long Gone by Tere Liye.